Pengembangan Media Pembelajaran Sembia Sosis Berbasis Android Untuk Siswa Sekolah Dasar - Siti Nur Paridotul Ramadhan; Rusi Rusmiati Aliyyah; Wilis Firmansyah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2022)
The purpose of this research is to produce an android-based learning media that can be used by sixth-grade elementary school (SD) students with the content of science subjects on theme 9 with material on the solar system. The background of this research is the boredom of students in implementing Distance Learning (PJJ) so that it requires interesting learning media that can be used anytime and anywhere offline. This research is a development research (R&D) using the ADDIE model procedure. Analysis of the data used is quantitative data analysis. The validation used is media and material validation carried out by experts in their fields. The respondents who were involved in testing the feasibility of the media included class VI teachers, and 20 elementary school students in class VI. The results of this study indicate that the Sembia Sosis (Happy Easy Learning Natural Sciences material for Solar Systems) application which was developed has the characteristics of a file in the form of an application package (apk) that can be installed and run using android that supports students to study independently. Based on the results of expert validation and respondents, overall it was concluded that the Sembia Sosis application suitable for use as a learning medium.